PENINGKATAN AKTIVITAS BELAJAR SISWA SD MELALUI PENGELOLAAN PEMBELAJARAN PROBLEM BASED LEARNING - Desy Primayani Rizana (UNIVERSITAS BENGKULU, 2017)
The aim of this research to increase the activities of students of grade 5th B Primary School 04 Kepahiang in learning management through problem based learning model. This research kind of classroom action research. According to the analysis of data on the activities of teachers and students in the learning has increased the average teacher activity by 79% with activity categories is good. While student activity cycle I and cycle II increased on average by 76% with the quality of good activity. With the gains of the analysis meets the specified criteria for the success of previously, which only reached 75%. Based on the results of the analysis can be concluded with the adoption of problem based learning model can increasing the students activities.